Emerging Insights into Noncanonical Inflammasome Recognition of Microbes - Russo, Ashley J. (J Mol Biol, 2017)
Inflammasomes are cytosolic multi-molecular complexes that sense intracellular microbial danger signals and metabolic perturbations. Inflammasome activation leads to the activation of caspase-1 and the release of pro-inflammatory cytokines IL-1β and IL-18 accompanied by cell death. An inflammasome-based surveillance machinery for Gram-negative bacterial infections has been recently discovered. This noncanonical inflammasome relies on sensing the cytosolic presence of lipopolysaccharide (LPS) of Gram-negative bacteria via inflammatory caspases such as caspase-4, -5, and -11. This Review discusses the recent findings related to the mechanism of activation of the noncanonical inflammasome and its biological functions.